2014
DOI: 10.1055/s-0034-1393698
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Upper Lip in Koreans

Abstract: The aims of this study were to provide the various dimensions of the philtrum and upper red lip in Korean young adults and to identify morphological characteristics of these structures in Koreans. A total of 10 dimensions of the philtrum and upper red lip were measured in 251 healthy young adults. Various indices were calculated among the measured features. The philtrum could be classified into three types according to its shape and index data. The mean height of the philtrum was 15.6 mm and the mean width of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
0
1
Order By: Relevance
“…The Phl/ICmD ratio indicates that the PhL is close to 1/3 of the mouth width. The PhL/ICmD ratio in our study were lower than those observed by Shin and Gil in adult Korean (0.36 in males and 0.32 in females) which also showed significant sexual dimorphism (Shin & Gil, 2014). The discrepancy in the results between the present study and that of Shin and Gil could be related to the difference in ethnic background and different age groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The Phl/ICmD ratio indicates that the PhL is close to 1/3 of the mouth width. The PhL/ICmD ratio in our study were lower than those observed by Shin and Gil in adult Korean (0.36 in males and 0.32 in females) which also showed significant sexual dimorphism (Shin & Gil, 2014). The discrepancy in the results between the present study and that of Shin and Gil could be related to the difference in ethnic background and different age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the PhL showed significant difference between males and females in most groups. This is in agreement with several studies (Nascimento, Cassiani, & Dantas, 2013;Ngeow & Aljunid, 2009;Shin & Gil, 2014). Regarding ICmD, several studies found significantly larger values in males compared to females (Amini, Mashayekhi, Rahimi, & Morad, 2014;Ngeow & Aljunid, 2009).…”
Section: Discussionsupporting
confidence: 93%